2013
DOI: 10.1007/s40003-013-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

How Important is the Quality of Organic Amendments in Relation to Mineral N Availability in Soils?

Abstract: Summary Wastes generated from municipal and agricultural activities have the tremendous potential for application in agriculture as a source of nutrients and as amendments to improve soil organic matter (SOM). A decline in SOM can represent a serious threat to soil fertility and quality. Nitrogen (N) mineralization from organic amendments is important for understanding the N dynamics in terrestrial ecosystems. In this review, quality of the amendments such as C/N ration, N content, and biochemical compositions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(45 citation statements)
references
References 104 publications
(81 reference statements)
1
27
0
3
Order By: Relevance
“…Increasing SOM by adding carbon is a beneficial agronomic practice that stimulates microbial communities and enhances soil N and C pools [31]. The youngest compounds are the most biologically active compounds, and the materials with intermediate ages contribute to soil physical characteristics [28]. We found positive correlations from GS37 to post-harvest with the N min values ( Table 3).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Increasing SOM by adding carbon is a beneficial agronomic practice that stimulates microbial communities and enhances soil N and C pools [31]. The youngest compounds are the most biologically active compounds, and the materials with intermediate ages contribute to soil physical characteristics [28]. We found positive correlations from GS37 to post-harvest with the N min values ( Table 3).…”
Section: Discussionmentioning
confidence: 76%
“…Nitrate production is mediated via two groups of autotrophic bacteria (Nitrosomonas and Nitrobacter) that convert ammonium into nitrate by the process called nitrification. Nitrogen availability relies on both the initial availability of N min and the rate of mineralization or immobilization [28], as well as the previous N uptake by the crop, influencing the yield and GPC.…”
Section: Discussionmentioning
confidence: 99%
“…We found these factors to significantly affect the microbial communities in Poyang Lake. Previous studies suggested that microbes use organic carbon as their main energy source while N is assimilated and metabolized during microbial growth as well as during the decomposition of the organic matter in the process of GHG production (Mohanty et al, ). Lin et al () have found that NH 4 + in water and in sediment could influence microbial processes at the sediment–water interface.…”
Section: Discussionmentioning
confidence: 99%
“…Kandungan bahan organik pada tanah vertisol pada umumnya rendah, yaitu berkisar 0,06 sampai 4,46% (Prasetyo, 2007), sedangkan C organik pada tanah vertisol ini tinggi, yaitu 3,9 % (Balittanah, 2005). Hal ini diduga karena adanya penambahan bahan organik pada saat pengolahan tanah sebelumnya, sehingga menyebabkan kandungan bahan organik pada tanah ini juga meningkat (Mohanty et al, 2013). Kandungan P dan K pada tanah vertisol ini tergolong rendah, yaitu 0,0178 ppm untuk P tersedia dan K tersedia 0,06 me/ 100 g. Rendahnya ketersediaan P mungkin disebabkan sebagian dari P diserap oleh kation Ca ++ , sedangkan K tersedia rendah diduga sedikitnya kandungan mineral feldspar (orthoklas, sanidin) dalam tanah (Prasetyo, 2007).…”
Section: Bahan Dan Metodeunclassified